Effect of age-appropriate visual aid on venipuncture on pain and anxiety levels among school age children - Banguilan, Lee B. (Manila: College of Nursing Library, University of the Philippines Manila, 2012)
Anxiety and pain are common negative psychological and physical consequences of painful medical procedure such as venipuncture. To help lessen these negative effects, one of the strategies recommended is to prepare the child by giving information about the procedure. This study sought to find out the effect of using an age-appropriate visual aid material in the form of flipchart, as a tool for pre-venipuncture preparation among school age children. This was compared to the traditional means which is giving information through verbal means. This study used the quasi-experimental pre and post-test design. Outcomes measured were anxiety using the State-Trait Anxiety Inventory for Children (STAIC) and pain using the Wong-Baker Faces Pain Scale. The computed sample size was 234 but only 65 study participants were recruited. Result showed that there was a significant decrease in anxiety among school age children who received pre-venipuncture information using the Visual Aid. However, there was no significant difference when compared with the traditional verbal instruction. Likewise, there was no significant difference in the pain scores of the two groups. It is therefore concluded that the use of age-appropriate visual aid material can significantly reduce anxiety among school age children for venipuncture; hence, its use as a pre-venipuncture preparation is recommended. One of the limitations of this study is the small sample size.
Thesis (Master of Arts in Nursing - Maternal and Child Nursing) -- University of the Philippines Manila, February 2012.
Bibliographic references: 75-83 leaves.
Keywords: Veins -- Puncture -- Visual aids; Veins -- Puncture -- School age (Entrance age).